HUBUNGAN ANTARA PERSALINAN KETUBAN PECAH DINI DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RSUD DR. SOESELO KABUPATEN TEGAL - Natiqotul Fatkhiyah (LPPM Universitas Pekalongan, 2011)
This was an analytic survey research is a study that tries to explore how and why health phenomena that occur. While the approach used is a cross sectional approach is to study the dynamics of correlation between risk factors with effects by way of approach, observation or data collection as well as at some point. Bivariate analysis results obtained with  2   2 count by 0.05 and db = 1, the obtained results  2 = 8.454 and p = 0.004 for values count more  2> 3.481 and p value <0.05, then the working hypothesis which states there is a relationship between premature rupture of membranes with acceptable incidence of asphyxia. It can be concluded that premature rupture of membranes variables significantly associated with incident asphyxia in newborns. the study following respondents who experienced PROM 23 people (21.3%) and did not experience there PROM 85 people (78.7%) respondents who experienced asphyxia there are 38 people (35.2%) and the did not experience there are 70 people asphyxia (64.8%); There was a significant correlation between premature rupture of membranes with asphyxia neonatorum in newborns is x2 value of 8.454 and p value = 0.004. Keywords: Premature Rupture Ketupan, Neonatorum Asphyxia, Birth Mother